Deep mapping the daily spaces of children and youth in the industrial city. Issue 4 (2nd October 2022) - Stone, Timothy; Lafreniere, Don; Hildebrandt, Rose
Abstract: Employing a deep mapping approach we aim to increase our understanding of the social, spatial, and temporal relationships children shared with the industrial city as it grew and evolved. In this paper, we spatialize and record-link numerous local and national datasets on environments and children including the complete count IPUMS historical census data to study the lives of schoolchildren in a twentieth century copper mining town in northern Michigan. Leaning on Hägerstrand's time geography theory we place 2025 children within their built and social environments tracing their commutes to school, the school day, and their time at home. We demonstrate the utility of this approach through an analysis of students' proximity to hazardous environments throughout the day.